'Has Anybody Seen a Tasmanian Tiger Lately?': Ethical and Ontological Considerations of Thylacine De-Extinction. Issue 1 (2nd January 2022) - Waterhouse, Jaxon; Mitchell, Chantelle
ABSTRACT: Considering animal futurity and changing more-than-human/human relationships, we mobilise the Tasmanian Tiger – the thylacine – to explore the implications of de-extinction. The thylacine's extinction is cause for speculation; questioned by those who see its ghostly traces across the landscape, and those who see it as a viable candidate for de-extinction. De-extinction entangles us within complex ethical and speculative territory. We suggest that species resurrection places the animal within a system of symbolic value, in which the animal is no longer an animal. It becomes unreal, as de-extinction necessitates the loss of the full depth of an animal's being in the world. The resurrected is instead a facsimile of being, a product of continued anthropogenic hubris. A species' importance is perceived to be tied to existence in context, and as such, we consider the significance of the thylacine's being, as symbol of extinction, martyr, or beacon of hope through de-extinction.